Baby Einstein: Neighborhood Animals - Marilyn Singer; Julie Aigner (Malasia Hyperion Books, 2001)
Children will discover the exciting world of their own backyard in this introduction to familiar animals from cats and dogs to bugs and frogs. The combination of photographs, illustrations, and fun facts make this an accessible and delightful learning experience.